Oral Squamous Papilloma: Unusual Size and Review of Literature - Alkananda Sahoo1, Priyanka Debta2, Satya Pattanaik3, Neeta Mohanty4, Debkant Jena5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oral squamous papilloma (OSP) specifies the non-neoplastic proliferation of stratified squamous epitheliumgiving rise to a verruciform or papillary growth on the surface of the oral cavity. Usually asymptomatic,OSP presents as soft tissue growth of the oral cavity exhibiting various clinical manifestations. Humanpapillomavirus (HPV) commonly HPV types 6 and 11 are believed to be the causative agents even thoughnot detected in some lesions. Found in 4 of every 1000 individuals OSP ranks fourth among the commonoral mucosal mass. It has equal predilection for both male and female and occurs within the age group of30 to 50 years. Its clinical appearance imitates exophytic carcinoma, verrucous carcinoma or condylomaacuminatum raising concern amongst the patient as well as the dental surgeon. OSP measures up to onecentimetre or so in diameter, but here we present a case where the lesion measures up to 5 centimetres indiameter along with review of literature.